The impact of trust towards online learning: study of Facebook among IM224 student in UiTM Kedah / Mohamad Rafiuddin Che Othman - Che Othman, Mohamad Rafiuddin (Faculty of Information Management, 2012)
The research was undertaken to examine the Impact of trust towards online learning: study of Facebook among form students from Bachelor of Science Library & Information Management (Hons) - IM220/IM224 in UiTM Kedah. The focus of this study was order to identify how trust as a factor that will influence online learning among students. The results of this research may help better understanding how trust among students affects online learning. The instrument for the study was a set of questionnaires. That was distributed to all Bachelor of Science Library & Information Management (Hons) IM220/IM224 student which about 145 students. There a one dependent variable and three independent variables for this research. The dependent variable is Online Learning: Facebook Intensity while independent variables are willingness, vulnerability and trustworthiness. The study revealed that 55.0% respondents think that willingness is an important factor that influences people in sharing of information or knowledge, 55.7% prefer to share information face to face rather than using other people and 58.6% of the respondents believe sharing information or knowledge with others can increase my knowledge and experience. Findings shows limitation and lack trust that make respondents unwilling to share their information and knowledge. There are four limitations that need to be during conducted this research which are time constrains, lack of related article, the honesty of the respondents and also financial.